Metaphorical Conceptualization of Food in Jordanian Arabic - Aljanada, Rose; Alfaisal , Aseel (International Journal of Language and Literary Studies, 2020)
This article studies the different food conceptual metaphors in Jordanian Arabic through the study of different food-related idioms and proverbs. A corpus was built by collecting the largest possible number of food-related idioms and proverbs used in Jordanian Arabic, regardless of the dialect, using a survey containing open-ended questions. The collected food-related idioms and proverbs were categorized according to the target domain into which the metaphors are mapped. Food in Jordanian Arabic food as a source domain can be mapped into the following target domains: IDEAS, EXPERIENCE, TEMPERAMENT, GAINING MONEY UNLAWFULLY, WINNING , DECEIVING, COOPERATION, SCHEMING and TALKING NONESENSE. These target domains form the following Conceptual Metaphors: IDEAS ARE FOOD, GOING THROUGH AN EXPEREINCE IS EATING IT, TEMPERAMENT IS FOOD, GAINING MONEY UNLAWFULLY IS EATING IT, WINNING IS EATING , DECEIVING IS MIXING INGREDIENTS, COOPERATION IS SHARING FOOD, SCHEMING IS COOKING TOGETHER and TALKING NONESENSE IS KNEADING.